2023
DOI: 10.3389/fhort.2023.1116866
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomics: a new tool for the generation of climate resilient grapevines

Abstract: Climate change is expected to increase the occurrence of extreme environmental conditions. Viticulture, as agriculture in general, is highly dependent on climatic conditions, not only for yield but also for fruit quality, which is the most important factor affecting produce value at the farm-gate. This demands the development of novel plant breeding techniques that will lead to the accelerated production of more resilient grape varieties, as conventional breeding programs for perennials are often prolonged. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 280 publications
1
8
0
Order By: Relevance
“…Enhancing our understanding of the epigenetic regulation of plant immunity may result in novel tools to strengthen natural defenses and thereby manage grapevine’s diseases and pests in an eco-friendly manner. Viticulture can also greatly benefit from understanding the mechanisms of transient and stable modifications in epigenetic memory for the development of new epi-breeding techniques for stress adaptation, such as targeted epigenetic modifications that can lead to more stress-tolerant cultivars [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing our understanding of the epigenetic regulation of plant immunity may result in novel tools to strengthen natural defenses and thereby manage grapevine’s diseases and pests in an eco-friendly manner. Viticulture can also greatly benefit from understanding the mechanisms of transient and stable modifications in epigenetic memory for the development of new epi-breeding techniques for stress adaptation, such as targeted epigenetic modifications that can lead to more stress-tolerant cultivars [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most epigenetic studies in grapevine have dealt with a single abiotic stressor (e.g., heat or drought), even though stress conditions in the environment usually occur in combination [ 14 , 53 ]. A recent study conducted with V. vinifera ‘Cabernet Sauvignon’ cv.…”
Section: Epigenetic Changes Due To Adverse Environmental Conditionsmentioning
confidence: 99%
“…Recent work has suggested that the environment can have a significant impact on the methylome and that environmentally induced epigenetic changes may be the molecular basis of the ‘terroir’ effect on grapevine development and product quality. Other studies have shown that the genotype is the primary driver of DNA methylation variability [ 39 , 99 , 100 ]. Collectively, these studies suggest that the combinatorial effect of genetic/epigenetic and environmental factors may shape the performance of distinct grapevine genotypes in diverse environmental regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the potential for epigenetic mechanisms contribution to domestication without genetic change 23-25 could provide novel insights into the early stages of domestication and the selective pressures faced by ancestral agriculturists. At the same time, such studies will lay the foundation for the development of comprehensive models integrating plant adaptation to the environment through epigenetics mechanisms, facilitating their use for the development of novel cultivars more resilient to stress 26 .…”
Section: Discussionmentioning
confidence: 99%